PENGARUH BELANJA PEMERINTAH DAN INDEKS PEMBANGUNAN MANUSIA TERHADAP INDEKS PEMBANGUNAN EKONOMI INKLUSIF - Ilyas, Israf; Prasetyia, Ferry (Journal of Development Economic and Social Studies, 2023)
The background of this study is the high economic growth in East Java for the last 5 years, but it remains the highest number of Poverty Rate in Java Island. This study purpose is to examine the influence of government spending on education function, health function, and economic function as well as HDI as the main variables on the inclusive Economic Development Index (IPEI). With GDP Growth and poverty rate as control variables. This study use Panel Data Regression Method in 38 cities/regencies in East Java during 2017-2021. The results showed that spending on health function and HDI had a significant positive effects on Inclusive economic growth. While spending on education & economic function had a positive yet insignificant effect on Inclusive economic growth.